Bleeding risk and drug interactions in patients with atrial fibrillation taking oral anticoagulants - Kovačević, Milena; Vezmar Kovačević, Sandra; Ćulafić, Milica; Jovanović, Marija; Vučićević, Katarina; Stevanović, Predrag; Radovanović, Slavica; Miljković, Branislava (Archives of Pharmacy, 2025)
Patients with atrial fibrillation (AF) have an increased risk of thromboembolic stroke and all-cause mortality. In addition to antiarrhythmic drugs, the treatment of AF also includes the use of anticoagulants, which significantly reduce the risk of ischaemic stroke, but also carry a bleeding risk. The aim of this study was to assess the risk of bleeding in patients with AF on oral anticoagulants, and to determine the frequency of potentially clinically significant drug-drug interactions (pDDIs) that may further increase the risk of bleeding. A retrospective observational study was conducted at the Department of Cardiology of the Clinical Hospital Center “Bežanijska Kosa”. The quantification of bleeding risk was performed using the HAS-BLED score. Lexi-Interact was used to identify pDDIs. The study included 124 patients (mean age 72 years, women 50.8%). A high risk of bleeding due to anticoagulant therapy was found in 10.5%. The prevalence of pDDIs, which can additionally increase bleeding risk was 18.5%. The pDDIs were combinations of vitamin K antagonists with selective serotonin reuptake inhibitors, proton pump inhibitors, levothyroxine, sulfonylureas, statins and propafenone. In the treatment and monitoring of patients with AF receiving oral anticoagulant therapy, the use of bleeding risk scores should be complemented by information on drug interactions, to optimise the benefit/risk ratio of anticoagulant therapy.